2022
DOI: 10.1126/science.abq7871
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and antiviral activity of a human protein of retroviral origin

Abstract: Endogenous retroviruses are abundant components of mammalian genomes descended from ancient germline infections. In several mammals, the envelope proteins encoded by these elements protect against exogenous viruses, but this activity has not been documented with endogenously expressed envelopes in humans. We report that the human genome harbors a large pool of envelope-derived sequences with the potential to restrict retroviral infection. To test this, we characterized an envelope-derived protein, Suppressyn. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 79 publications
(45 reference statements)
0
46
0
Order By: Relevance
“…Because their origins and underlying virological functions are well understood, ERV-encoded Env glycoproteins can serve as model systems for understanding the phenomenon of evolutionary cooption and the events that occur after germline integration of an env gene, such as acquisition and fine-tuning of host-cell regulatory mechanisms, integration within the regulatory networks of other interacting host genes, and further adaptations of the encoded Env protein for optimal host function [ 25 , 27 ]. For example, decades of work on exogenous viruses such as MLV-guided identification of the fusion defects in the murine Fv4 and human envHERV-T viral resistance proteins [ 66 , 69 , 72 ]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because their origins and underlying virological functions are well understood, ERV-encoded Env glycoproteins can serve as model systems for understanding the phenomenon of evolutionary cooption and the events that occur after germline integration of an env gene, such as acquisition and fine-tuning of host-cell regulatory mechanisms, integration within the regulatory networks of other interacting host genes, and further adaptations of the encoded Env protein for optimal host function [ 25 , 27 ]. For example, decades of work on exogenous viruses such as MLV-guided identification of the fusion defects in the murine Fv4 and human envHERV-T viral resistance proteins [ 66 , 69 , 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Ancient endogenous retrovirus (ERV) loci often contain remnants of retroviral env genes, and in some cases, these may retain complete or nearly complete open reading frames with the potential to express functional gamma-type Env proteins [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Gammaretrovirus-related ERV loci are abundant in the genomes of a diverse array of vertebrate species, including mammals, birds/reptiles and amphibians [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the receptor for SynA, lymphocyte antigen 6 family member E (Ly6e), is highly expressed in murine spleen (in addition to liver, lung, and placenta) and mediates cell-cell fusion upon binding with SynA, [18][19][20] which suggests that fusogens like SynA and SynB could be involved in SEND-VLP phenomenon in spleen but again our experiments may not have been sensitive enough to detect it. In addition, recent studies have reported several genes that reduce cell-cell fusion efficiency of endogenous retroviral envelope genes by interfering their receptors in humans 21,22 and various primates. 23 While no interfering elements have been reported for SynA and SynB, they may also be involved in transduction efficiency.…”
Section: Discussionmentioning
confidence: 99%